MANAJEMEN ANGGARAN PENDAPATAN DAN BELANJA DESA DI DESA LIWUTUNG KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA - GINSU, ADRIANUS; POSUMAH, JOHNNY; TAMPI, GUSTAAF (JURNAL ADMINISTRASI PUBLIK, 2019)
The purpose of this study was to find out how the APB-Village management in LiwutungVillage, Pasan District, North Minahasa Regency. This study uses a descriptive-qualitative approach. Thefocus of the research is planning the APB-Desa, organizing the implementation of the APB-Desa,mobilizing resources for the implementation of the APB-Desa, and overseeing the APB-Desa. The researchinformants were the Village Head, BPD Chair, Village LPMetaris Chair as PTKD coordinator, head offinancial affairs / village treasurer, community leaders. Data collection uses interview guidelines, while theanalysis technique used is the analysis of interactive models from Miles and Hubernann. The results of thestudy provide conclusions: (1) Planning of the APB-Desa is done quite well in accordance with theapplicable laws and regulations. Discussion and Determination of the APB-Village is carried out throughvillage head meetings with BPD, and also involves LPMD and community group representatives. Theallocation of APB Desa is appropriate. (2) Organizing the implementation of the APB-Desa was carried outquite well, where an APB-Village drafting team was formed and the Village Financial ManagementTechnical Implementation Team (PTKD). (3) The mobilizer for the implementation of the APB-Desa iscarried out by the village head reasonably well where the village officials are functioned according to theirrespective positions / authorities in the implementation of the APB-Village. (4) Supervision of theimplementation of the APB-Desa goes quite well. The Camat on behalf of the Bupati evaluates the draftAPB-Desa before it is determined to be a Village Regulation. The BPD has also functioned quite well insupervising the implementation of the APB-Desa in accordance with the functions and authorities possessedas supervisory institutions in the village.Keywords: Management, Revenue and Expenditure Budget, Village